Fostering student questioning in Islamic education: The learning start with a question strategy in a vocational high school - Annisa Salsabila Firdausia; Chairul Anwar; Era Octafiona (STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to analyze the planning, implementation, and supporting and inhibiting factors of the Learning Start with a Question (LSQ) strategy in fostering student questioning in Islamic Religious Education at a vocational high school, SMKN 1 Kebun Tebu. Although previous research shows that student-centered strategies improve engagement, limited attention has been given to how LSQ specifically fosters questioning skills in Islamic Religious Education within vocational schools. Few studies have examined its planning and implementation challenges in this setting. This qualitative case study involved students and an Islamic Religious Education teacher. Data were collected through observations, interviews, and documentation. Findings show LSQ was implemented through structured stages: providing learning stimuli, student-generated questions, class discussions, and teacher reinforcement. Student participation increased noticeably, from only a few students asking questions initially to many more actively participating after several meetings. The strategy gradually fostered students' questioning skills in relevance, clarity, and depth, with some students demonstrating higher-order thinking, though variations remained. To address initial shyness, the teacher used written questioning and small-group discussions, which engaged previously passive students. However, a small number remained less active, indicating the need for continued support. Supporting factors included contextual media and active teacher facilitation, while cognitive ability differences remained a challenge. This study provides empirical evidence and a practical implementation model of LSQ for Islamic Religious Education teachers in vocational schools.